Association between oxidative balance score and new-onset hypertension in adults: A community-based prospective cohort study - Lee, Jun-Hyuk; Son, Da-Hye; Kwon, Yu-Jin (Frontiers in Nutrition, 2022)
Introduction Oxidative stress plays a key role in the pathophysiology of hypertension development. The oxidative balance score (OBS) comprises dietary and lifestyle pro- and anti-oxidant components and reflects the overall oxidative stress burden. We aimed to evaluate the association between the OBS and new-onset hypertension (HTN) using large, community-based, prospective Korean cohort data. Methods Among 10,030 participants aged 40–69 years included in the Korean Genome and Epidemiology Study, the data of 5,181 participants were analyzed. The hazard ratio (HR) and 95% confidence interval (CI) for new-onset HTN according to sex-specific OBS quartile groups were calculated using univariable and multivariable Cox proportional hazard regression analyses. Results During the mean 13.6-year follow-up period, 1,157 men and 1,196 women developed new-onset HTN. Compared to the Q1 group, the adjusted HRs (95%CI) for new-onset HTN in the Q2, Q3, and Q4 groups were 0.96 (0.82–1.16), 0.85 (0.72–0.99), and 0.71 (0.59–0.86) in men and 0.81 (0.69–0.95), 0.81(0.68–0.95), and 0.70 (0.57–0.84) in women, respectively. Discussion Individuals with high OBS are at lower risk of developing HTN. This study suggests that a healthy lifestyle and antioxidant rich diet could be a preventive strategy for HTN.